AKTUALISASI NILAI MODERASI BERAGAMA PADA GENERASI Z MELALUI PENDIDIKAN AGAMA ISLAM - Zainul Muflihin (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
Generation Z, as a group that grew up in the digital and globalization era, faces serious challenges in the form of rapid information flows, the penetration of transnational ideologies, and tendencies toward religious exclusivism. In this context, Islamic Religious Education (IRE) plays an important role as a medium for actualizing the values of religious moderation, which include tolerance, justice, balance, and anti-violence. This study employs a library research approach, examining various literature, government regulations, and previous research findings related to the implementation of religious moderation in education. The findings indicate that the values of moderation can be integrated into the IR curriculum, participatory learning methods, extracurricular activities, and the utilization of religious digital literacy. Additionally, PAI teachers play a strategic role as role models capable of instilling inclusive, dialogic, and tolerant attitudes in students. Through the actualization of religious moderation values, PAI can shape Generation Z into individuals who are not only religious but also possess social capacity as agents of peace and guardians of national unity amid Indonesia's pluralistic society.